O que motiva os sujeitos de diferentes grupos sociais a visitarem o Museu de Artes e Ofícios de belo Horizonte - MG - Thiago Lucas Rodrigues Martins (2015)
This research has the intention to understand what motivates individuals from different social groups to visit the Museu de Artes e Ofícios de Belo Horizonte (Museum of Arts and Crafts of Belo Horizonte) - MG (MAO). Based on the concepts of cultural capital and habitus built by Pierre Bourdieu, and on the sociology of Bernard Lahire, especially his concept of plural actor, we seek to investigate the extent to which social origin, education level, frequency of cultural practices and social relationship with friends and / or co-workers, could influence a visit to the Museu de Artes e Ofícios. To understand the reasons for the visits we applied between August and November 2014, 28 semi-structured interviews with subjects who visited the museum without prior appointment; ie, people who were to the MAO space spontaneously. The data analysis was divided into two parts. In the first stage of the analysis all the information obtained from interviews involving the education of individuals, parents' education and the frequency to other museums, theater, cinema and concerts were tabulated. In the second stage of the analysis we selected 13 interviews to be analyzed individually. These subjects were divided into three groups: individuals who were passing through the Praça da Estação and visited the MAO, visitors who were bringing family or friends to know the Museu de Artes e Ofícios and visitors who came to MAO by direct influence of the school. Through the reasons given to visit the Museu de Artes e Ofícios it was possible to grasp the discourses that the subjects used to justify or legitimize their presence in the museum. The research allows us to understand that the visit to MAO is not necessarily associated with a cultivated disposition. One of the reasons that lead individuals to the museum is the theme of the collection that somehow is similar to the social histories of individuals.